Гнучкі сонячні елементи - Мазченко, К. А. (ХНУРЕ, 2023)
The main element of solar power plants are solar panels. The development of modern technologies leads to the emergence of new types of solar panels, namely flexible ones. This paper examines the main types of solar panels. Their types, structure, materials from which they are made. The paper presents the advantages and disadvantages of flexible panels. The efficiency of solar panels of different types is compared